A Grid in Flux: Sound and Timing in Electronic Dance Music. (9th December 2021) - Brøvig-Hanssen, Ragnhild; Sandvik, Bjørnar; Aareskjold-Drecker, Jon Marius; Danielsen, Anne
Abstract: Researchers have argued that temporal microdeviations from the metric grid, such as those produced by musicians in performance, are crucial to making a musical rhythm groovy and danceable. It is curious, then, that the music currently dominating the dance floor, "electronic dance music" or EDM, is typically characterized by grid-based rhythms. But is such a "mechanistic, " grid-based aesthetic necessarily devoid of microrhythmic nuance? In this article, we aim to show that the microrhythmic component of an engaging groove involves the manipulation of more than simply the onset locations of rhythmic events—the sonic features fundamentally contribute to shaping the groove as well. In particular, we seek to demonstrate that EDM producers, with their preference for a grid-based microtiming aesthetic, are very sensitive to and adept at manipulating such sonic features for expressive effect. Drawing on interviews with EDM producers, we show that producers are often concerned with both sonic and temporal features, as well as their interactions. We argue that sonic features are crucial to shaping groove and feel at the micro level of rhythm. Moreover, such features also tend to introduce an indirect microtiming aspect to the grid-based aesthetic of EDM through the ways in which they shape timing at the perceptual level.